2020
DOI: 10.1111/1755-6724.14559
|View full text |Cite
|
Sign up to set email alerts
|

Early Paleozoic Ocean Plate Stratigraphy of the Beishan Orogenic Zone, NW China: Implications for Regional Tectonic Evolution

Abstract: The Beishan orogenic zone is a key area to understand evolution of the Central Asian Orogenic Belt that is an accretionary factory well‐enough preserved in the Paleozoic. In early Paleozoic, the tectonic mélange zone containing the coherent unit and mélange unit is triggered by the complicated accretionary process of the Beishan area. The early Paleozoic tectonic evolution of the Beishan orogenic zone is investigated in this study using sedimentology and stratigraphic correlations of the lowe Paleozoic deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Combined with the discoveries of numerous magmatic rocks with zircon U-Pb ages of 466 to 447 Ma (Hu et al, 2008;Wang et al, 2012) in the northern BY, it is suggested that the initial southward subduction of the northern Tianshan Ocean began in the Middle Ordovician (Huang Z Y et al, 2013), and terminated in the latest Early Carboniferous . Contrastingly, the STAC was related to the northward subduction of the southern Tianshan Ocean and Late Paleozoic collision between the Tarim Craton and the BY-CTAT (Li et al, 2018a), an event which is characterized by a highultrahigh pressure (HP-UHP) metamorphic belt and associated ophiolitic mé langes (Gao and Klemd, 2003;Zhang et al, 2013;Zhang et al, 2020). The metamorphic belt is dominated by metapelites, eclogites, blueschists and marbles (Gao and Klemd, 2003), with the peak metamorphism time probably representing an important orogenic event (Su et al, 2010).…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with the discoveries of numerous magmatic rocks with zircon U-Pb ages of 466 to 447 Ma (Hu et al, 2008;Wang et al, 2012) in the northern BY, it is suggested that the initial southward subduction of the northern Tianshan Ocean began in the Middle Ordovician (Huang Z Y et al, 2013), and terminated in the latest Early Carboniferous . Contrastingly, the STAC was related to the northward subduction of the southern Tianshan Ocean and Late Paleozoic collision between the Tarim Craton and the BY-CTAT (Li et al, 2018a), an event which is characterized by a highultrahigh pressure (HP-UHP) metamorphic belt and associated ophiolitic mé langes (Gao and Klemd, 2003;Zhang et al, 2013;Zhang et al, 2020). The metamorphic belt is dominated by metapelites, eclogites, blueschists and marbles (Gao and Klemd, 2003), with the peak metamorphism time probably representing an important orogenic event (Su et al, 2010).…”
Section: Geological Settingmentioning
confidence: 99%
“…The Central Asian Orogenic Belt (CAOB) represents the largest Phanerozoic accretionary tectonic orogen in the world (Jahn et al, 2004;Windley et al, 2007;Shen et al, 2008), and is mainly composed of a series of microcontinents, island arcs, seamounts, and ophiolitic mé langes (Xiao et al, 2014;Yang et al, 2015;Wang et al, 2020). The formation of the CAOB was closely associated with the gradual contraction and final closure of the Paleo-Asian Ocean (PAO) (Wilhem et al, 2012;Li et al, 2013;Li S et al, 2016), and its closure displayed diachronous characteristics in different areas (Li et al, 2013;.…”
Section: Introductionmentioning
confidence: 99%